"Against the Grain": How Music Journalism Frames Bad Religion as Unconventional. Issue 3 (1st September 2016) - McClain, Jordan M.; Bernhard, Ellen M.
Abstract : This article examines media coverage of the punk rock band Bad Religion (1979–present) and uses theory about media framing to understand how the band is characterized and consequently framed as unconventional. A textual analysis examined 174 magazine articles from thebrpage.net, an extensive fan-curated collection of media coverage about the band. The study found that Bad Religion are framed as unconventional through various techniques, including focus on singer Greg Graffin's PhD degree, the band's role in noted punk label Epitaph Records, and their decades-long career. The findings indicate much about the way music journalism operates and constructs our world.